DIPG-82. CLINICAL EXPERIENCE OF CONVECTION ENHANCED DELIVERY (CED) OF CARBOPLATIN AND SODIUM VALPROATE INTO THE PONS FOR THE TREATMENT OF DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) IN CHILDREN AND YOUNG ADULTS AFTER RADIOTHERAPY. (4th December 2020) - Szychot, Elwira; Walker, David; Collins, Peter; Hyare, Harpreet; Shankar, Ananth; Bienemann, Alison; Hollingworth, Milo; Gill, Steven
Abstract: PURPOSE: Effective treatment of diffuse intrinsic pontine glioma (DIPG) remains a formidable challenge due to inadequate penetration of the blood-brain barrier (BBB) by systemically administered chemotherapies. The BBB can be overcome by directly infusing drugs into pons using method of convection-enhanced delivery (CED). We describe our clinical experience and what we have learned about the safety and feasibility of treating DIPG with intermittent CED of carboplatin and sodium valproate to the pons through the Renishaw Drug Delivery System (RDDS). METHODS: Retrospective review (2017–2020) of children with DIPG, who following radiotherapy, received compassionate treatment commencing 3.3–10 months post diagnosis (median 4.9 months). They received up to 7 cycles of 3–6 weekly pontine infusions of carboplatin (0.12-0.18mg/ml) and sodium valproate (14.4- 28.8mg/ml). RESULTS: 13 children 3–19 years (mean 6.9 years) were treated. There were no surgical complications. With the exception of infusion channels blocking in one device there were no adverse device effects. Two patients developed persistent 6 th nerve palsies, which led to drug concentration reduction in the combination therapy. Subsequently infusion/ drug related toxicities were transient. Tumour was controlled in pons in 11/13 patients. Median progression free survival (PFS) was 13.0 months, while median overall survival (OS) was 15.3 months. CONCLUSIONS: Use of the RDDS was safe and well tolerated in all 13 patients. Treatment improved control of pontine disease resulting in longer PFS and OS than reported for conventional therapy and merits further evaluation in a clinical trial.